Rethinking international student mobility within higher education internationalization: A systematic literature review and outcome-driven model - Sinha, Anushka; Sharma, Dr. Adya; Panackal, Nehajoan (Journal of International Students, 2026)
The internationalization of higher education has become a priority for institutions worldwide, as it enhances academic quality, promotes global knowledge exchange, and strengthens institutional credibility. Within this context, international students play a central role in driving cross-border mobility and shaping global education systems. However, research shows that, in developing economies, the proportion of international students who participate in mobility remains lower than that in developed countries. A review of the literature further reveals a lack of research examining the interconnections among international student mobility, sustainability, and internationalization within the Sustainable Development Goals framework. To address these gaps, the present study conducts a systematic literature review of 79 research articles indexed in Scopus and Web of Science.